Response to Nitrogen and Phosphorus Fertilization in Lignocellulosic Crops - Viana Otero, María Virginia; Siri Prieto, Guillermo (Agrociencia Uruguay, 2019)
Lignocellulosic crops have been developed as an alternative in the energy matrix. Three species of interest in Uruguay are Arundo donax, Pennisetum purpureum and Panicum virgatum. In these crops nitrogen fertilization is the largest energy input. The objective was to compare the production of these three species, quantify the response to the addition of nitrogen and phosphorus and compare the final carbon content in the soil. The cultures were installed in 2007 and were evaluated from September 2011 to August 2013. The fertilization treatments after cutting were: witness without fertilization; 100 kg ha-1 N; 100 kg ha-1 of P2O5; and 100 kg ha-1 of N and P2O5. The production was higher in 2013. Arundo donax, with a production of 18.6 Mg ha-1 y-1, produced more than P.purpureum, with a production of 14.9 Mg ha-1 y-1, while P. virgatum had intermediate values, 15.6 Mgha-1y-1. N fertilization increased production by 50% in the three species, though in A. donax the increase was not significant. There was no response to fertilization with P. Differences in biomass production did not generate differences in soil carbon content at the end of the evaluation. In spite P. virgatum intermediate yield, it was the species with the lowest moisture content (16 %), which is favorable as raw material for energy production. The yield were the expected ones for our region, with an annual variability attributable to climatic conditions and that can be increased with N fertilization.